Anorectal and Urogenital Mycoplasma genitalium in Nigerian Men Who Have Sex With Men and Transgender Women: Prevalence, Incidence, and Association With HIV. Issue 3 (March 2020) - Crowell, Trevor A.; Lawlor, John; Lombardi, Kara; Nowak, Rebecca G.; Hardick, Justin; Odeyemi, Sunday; Kokogho, Afoke; Malia, Jennifer; Stewart, Catherine; Robb, Merlin L.; Baral, Stefan D.; Adebajo, Sylvia; et al.
Abstract : Abstract: Among 413 Nigerian men who have sex with men and transgender women, retrospective testing for Mycoplasma genitalium revealed mostly asymptomatic infections of the anorectum (prevalence, 36.8%; incidence, 18.4 cases/100 person-years) and urogenital tract (12.4%, 4.0 cases/100 person-years). Risk factors included HIV and increasing number of sex partners. Abstract : A study of Nigerian men who have sex with men and transgender women found that more than one-third had anorectal Mycoplasma genitalium . HIV was independently associated with M. genitalium infection.Supplemental digital content is available in the text.